DIAGNOSA HAMA DAN PENYAKIT PADA TANAMAN CABAI MENGGUNAKAN METODE VARIABLE CENTERED INTELLIGENT RULE SYSTEM (VCIRS) - Daud Meko; Derwin R Sina; Kornelis Letelay (Universitas Nusa Cendana, 2018)
This research led to an expert system application that was built by applying the method variable centered intelligent rule system and the certainty factor. Variable Centered Intelligent Rule System (VCIRS) is an intelligent rule-based system that focuses on the variables. VCIRS procedures are able to take over the construction of knowledge, update knowledge as well as advice or inference process. Procedure own certainty factor on the symptoms of pests or diseases taking into account the weighting process used to provide from the weighting process result in the form of pests or diseases to the value of the trust of the system. The location of this research is located in Rote Ndao Regency. Data used in this application testing of 28 case data sourced from an expert or agricultural expert. Accuracy in this study was 100 %. The results showed that the method variable centered intelligent rule system and certainty factor can be applied in the application of expert system for the diagnosis of plant pests and diseases chili.